Effects of raloxifene use on cardiovascular disease risk determinants in postmenopausal women - Ciftci, Banu; Guner, Haldun (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Raloxifene is a selective estrogen receptor modulator (SERM) that binds to estrogen receptors with high affinity, acting as an estrogen agonist or antagonist in a tissue-specific manner. This study aimed to evaluate the effect of raloxifene on various cardiovascular risk determinants in postmenopausal women and to compare these effects with those in a control group. Methods: The study was conducted as a prospective, open, matched case-control study at Gazi University Hospital. A total of 100 postmenopausal women were included. Fifty postmenopausal women with osteoporosis received 60 mg of raloxifene daily. The other fifty healthy postmenopausal women in the control group received no treatment. After one year, changes in cardiovascular risk markers compared to baseline values were evaluated in both the treatment and control groups. The plasma determinants evaluated included total cholesterol, LDL, HDL, triglycerides, lipoprotein (a), Apo A, Apo B, homocysteine, hs-CRP, and fibrinogen. Carotid intima-media thickness, an important radiologic indicator of cardiovascular risk, was also measured and compared between the groups. Results: After the study, raloxifene was found to decrease levels of total cholesterol, LDL, homocysteine, and fibrinogen, but it did not affect HDL, triglyceride, Apo B, lipoprotein (a), and hs-CRP levels. There were no differences between the baseline values of the groups or the values of the control group after the study period. In the control group, there was a significant increase in carotid intima-media thickness compared to baseline values, while no such difference was observed in the raloxifene group. Conclusions: Raloxifene caused favorable changes in many biochemical and radiologic cardiovascular risk determinants compared to the control group. Further clinical studies are needed to determine whether these effects are associated with cardiovascular protection.